Clinical activity of everolimus in relapsed/refractory marginal zone B‐cell lymphomas: results of a phase II study of the International Extranodal Lymphoma Study Group. (27th March 2014) - Conconi, Annarita; Raderer, Markus; Franceschetti, Silvia; Devizzi, Liliana; Ferreri, Andrés J. M.; Magagnoli, Massimo; Arcaini, Luca; Zinzani, Pier Luigi; Martinelli, Giovanni; Vitolo, Umberto; Kiesewetter, Barbara; Porro, Elena; et al.
Summary The International Extranodal Lymphoma Study Group coordinated a phase II trial to evaluate the activity and safety of everolimus in marginal zone lymphomas (MZLs). Thirty patients with relapsed/refractory MZLs received everolimus for six cycles or until dose‐limiting toxicity or progression. Median age was 71 years (range, 51–88 years). Twenty patients had extranodal, six splenic, four nodal MZL. Twenty‐four patients had stage III–IV. Median number of prior therapies was two (range 1–5). Seventeen patients had early treatment discontinuation, in most cases due to toxicity. Median number of cycles was 4·5 (range, 1–16). Among the 24 assessable patients, the overall response rate (ORR) was 25% (95% confidence interval: 10–47). Grade 3–4 adverse events were neutropenia and thrombocytopenia (17% of patients, each), infections (17%), mucositis and odontogenic infections (13%) and lung toxicity (3%). The median response duration was 6·8 months (range, 1·4–11·1+). After a median follow‐up of 14·5 months, five deaths were reported: four deaths were due to lymphoma, one was due to toxicity. In an intent‐to‐treat analysis, the projected median progression‐free survival was 14 months. The moderate antitumour activity of everolimus in relapsed/refractory MZLs and the observed toxicity limit its therapeutical applicability in these indolent entities. Lower doses of the drug and, perhaps, different strategies including combination with additional agents need to be explored.